Maintaining efficiency while integrating entrants from lower-performing groups: An experimental study - Timothy C. Salmon; Roberto A. Weber (University of Zurich, Department of Economics, 2014)
Efficiently growing a group or firm often requires integration of individuals from lower-performing entities. We explore the effectiveness of two policies intended to facilitate such integration, using a laboratory experiment that models production as a coordination game with Pareto-ranked equilibria. We initially create an efficient group and an inefficient one. We then allow individuals to move into the high-performing group and vary by treatment whether movement is unrestricted, limited to one entrant per period, or subject to an entry exam. We include two additional treatments that combine the two restrictions in different ways to help understand why the institutions are effective in maintaining coordination. We find that both restrictions work to maintain efficient coordination but they are effective for different reasons.
Keywords: C72; C92; M12; 330; Growth; Entry; Coordination; Experiments; Gruppenentscheidung; Mitgliedschaft; Soziales Verhalten; Nichtkooperatives Spiel; Test